Transitional justice (Revista de Investigaciones Universidad del Quindío, 2021)
In each nation, elements of conflicts are identified that allude to violating or violating human rights, transgressing the dignity of the person. The justice administration system must consider substantial elements to respond effectively and promptly to it. In this sense, the recognition and validity of the rules of external and internal origin provide guidelines for exercising and guaranteeing the rights recognized in the Magna Carta of the Mexican state. In this sense, this document deals with general aspects of transitional justice in a descriptive way, with the aim of ensuring that those responsible prove responsibility for their actions, justice exists and reconciliation is achieved; For this, the internal justice system must have a coalition in the mechanisms of access and administration of heterocompositive and self-compound justice.
Keywords: human rights; dignity; justice; reparation; truth